A Study of the Laws of Abnormal Gas Emissions and the Stability Controls for Coal Mine Walls in Deeply Buried High-Gas Coal Seams - Anying Yuan; Hao Hu; Qiupeng Yuan (Advances in Civil Engineering)
At the present time, it is considered to be of major significance to study the gas emission law and stability controls of coal bodies in deeply buried high-gas coal seams. For this reason, in view of the specific problems of gas emissions caused by unstable rib spalling in coal mine walls, comprehensive research methods were adopted in this study, in order to conduct an in-depth examination of micropore structure parameters, gas desorption, diffusion laws, and coal stability levels. The results showed that the development degree of the pores above the micropores, as well as the small pores in soft coal seams, was better than those observed in hard coal seams. In addition, the gas outburst phenomenon was found to have more easily formed in the soft coal seams. The coal body of the No. 6 coal seam in the Xieqiao Coal Mine not only provided the conditions for gas adsorption but also provided dominant channels for gas diffusion and migration. The abnormal gas emissions of the No. 6 coal seam were jointly caused by the relatively developed pores above the small holes in the coal body, rib spalling of coal mine walls, and so on. The research results also revealed the evolution law of mechanical characteristics of the No. 6 coal seam under different water content conditions. It was found that the strength levels of the No. 6 coal seam first increased and then decreased with the increase in water content, and the water content level at the maximum strength of the coal seam was determined to be 7.09%. This study put forward a method which combined the water injection technology of long-term static pressure water injections in deep coal mining holes and real-time dynamic pressure water injections in shallower holes. Field experiments were successfully carried out.